Investigation on properties of part fabricated by selective laser sintering (SLS) process - soundrapandian, E.; SenthilKumar, G.; Tajdeen, A.; Vivekkumar, P. (International Journal of Engineering and Technology, 2018)
Additive manufacturing (AM) can be used without the need of any moulds or tooling, and are very suitable for manufacturing one-piece or small batches of with complex external shapes and internal structures within a short lead time, which are difficult to make or even cannot be fabricated by the tooling and machining processes. The manufacturing of metal parts by sand casting method is a tedious process when considering low volume manufacturing where it took lot of time, design cost, material cost etc., In this paper, the web gland component has been prepared using stainless steel by varying the different process parameters such as scan spacing, laser power and layer thickness in selective laser sintering (SLS) process. By using vickers hardness tester, the hardness and the microstructure of component also analyzed and it is compared with the same component properties prepared by using sand casting process. From the comparative result, it was found that the hardness of material increases by 12.5% on sintered part than casting part.Â Â